Screening Of Dermatophyte Fungi on Nails of Scavengers of Antang Makassar Final Disposal Site - Ramadhan, Etta hamid; Hartati; Waji , Resi Agestia (Program Studi Teknologi Laboratorium Medis, 2025)
The landfill is a landfill that is known for its humid and dirty environment so that it can pose a risk for people living in the area to be infected with nail fungus. This study aims to conduct screening or initial examination to find out if there is dermatophyte fungus on scavenger's nails. The research was descriptive as many as 10 samples of scavenger nails obtained by purposive sampling technique and examined at the DIII Tropical Infection Laboratory, Medical Laboratory Technology, Megarezky University, Makassar. The examination methods used are the direct method and the culture method. Based on the identification using the direct method, it showed that there were no hyphae or spores (negative) and continued with the culture method and obtained the results of 6 samples there were dermatophyte fungi, namely Trichophyton rubrum, Epidermophyton flocossum, and Microsporum gypseum. There were six people infected with fungus on the nails and the fungal species were Trichophyton rubrum, Epidermophyton flocossum, and Microsporum gypseum.